New geological insights on the Palaeoproterozoic Sembé-Ouesso Basin in northern Congo-Brazzaville – implications for the Kibaran orogeny, Neoproterozoic rifting and Pan-African overprint - (:unkn) unknown (My University, 2024)
The Palaeoproterozoic Sembé-Ouesso Basin (SOB) is the northeasternmost of six foreland subbasins of the Eburnean orogen; it covers an area of about 64,000km2 in the northern Republic of Congo, southeast Cameroun and the Central African Republic. The structural architecture and tectono-metamorphic history of the SOB have been studied in the Republic of Congo by airborne geophysical interpretation, geological mapping, and petrography, analysis of illite crystallinity and K-Ar geochronology.The oldest tectono-metamorphic event (D1/M1), which caused the main structuring of the SOB, coincides in age with the last (1.0-1.07 Ga) stage of Kibaran orogeny. Metamorphic conditions decrease from greenschist facies in the east to upper diagenesis in the west. D1 deformation started with west-vergent folding followed by N-S sinistral transpression in discrete shear zones. The tectonic style characterises the SOB as foreland in the external zone of an eastern concealed orogen that either represents the continuation of the Kibaran Belt or forms a separate, as yet unidentified unit.Subsequent Neoproterozoic extension is marked by two conjugate N-S/NNE-SSW and E-W/NW-SE fault systems and a local pull-apart structure (D2). Coeval mafic magmas were emplaced in the faults of both systems. At regional scale, the extension can be linked to Tonian rifting in the central part of the Congo Basin and within the West Congo Belt.The influence of the Neoproterozoic (600 Ma) Central African orogeny is mainly restricted to the north-western part of the SOB where the Dja nappe was thrust from the north over the Palaeoproterozoic rocks (D3/M2). Elsewhere, the Pan-African event had no thermal and only minor structural effects on the SOB.
Keywords: African Research